Left ventricular diastolic dysfunction in primary hypertension and ischemic heart disease-evaluation by doppler echocardiography - Kumar, Rahul; Diwakar, Sanjeev; ., Srinivas (International Journal of Advances in Medicine, 2021)
Background: Congestive heart failure caused by a predominant abnormality in diastolic function is both common and causes significant morbidity and mortality. The objective of the study was to evaluate application of doppler echocardiography in determining left ventricular diastolic dysfunction in ischemic heart disease and essential hypertension. Methods: Present study is based on analysis of 75 patients of hypertension and 60 patients of IHD (UA, AMI, IMI) admitted to Bapuji and Chigateri general hospital during December 2019 to November 2020. Detailed history and physical examination were done. Every patient was subjected to ECG, CXR, routine investigations and Doppler Echo cardiography. Results: A total of 75 patients of primary hypertension were studied. 37 patients showed diastolic dysfunction with E/A ratio <1, with increased atrial filling fraction. Out of 37 patients, 24 showed LVH and 13 cases did not have LVH. A total of 60 patients of ischemic heart disease were studied. 23 patients showed diastolic dysfunction with E/A ratio <1, with increased atrial filling fraction and prolonged isovolumetric relaxation time. Conclusions: Our findings suggest that myocardial damage in patients with HTN and IHD affects diastolic dysfunction before systolic dysfunction. Doppler echocardiography is a valuable non-invasive method to detect left ventricular diastolic impairment and the intentional assessment of diastolic function is advisable for early detection of LV dysfunction before clinical symptoms appear.